Ethnoscience Study of Reed Plants (Imperata Cylindrica (L.)) in the Ume Kbubu of the Timor Tribe - Baifeto, Ekri Pranata Ferdinand; Sriyati, Siti; Liliawati, Winny; Tohe, Humairah Ansar (Chemistry Education Department, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga, 2024)
The alang-alang plant is believed to be a good thermal insulation, but unfortunately, it is starting to be abandoned. The purpose of this study was to investigate the use of reed plants (Imperata cylindrica (L.)) as a basic material in the manufacture of ume kbubu of the Timorese tribe. This research was conducted in the South Middle Timor District, East Nusa Tenggara Province. The method used in this research is the triangulation method, which analyzes primary data in the form of observation data, interview data, and literature studies. The results showed that alang-alang (Imperata cylindrica (L.)) is used by Timorese people as an ume kbubu roof due to several factors such as its abundant availability, cheap, strong, durable, and cheap. Through scientific studies, it can be explained that alang-alang (Imperata cylindrica (L.)) has a strong structure, contains high lignin and cellulose, is hydrophobic, and has anti-microbial and antioxidant properties that can help protect plants from pests and diseases. In addition, the influence of the shape of the roof construction using alang-alang which has a hollow structure makes the ume kbubu roof a good thermal insulator. The study of community science and scientific science on using reeds (Imperata cylindrica (L.)) as a basic material for making ume kbubu of the Timorese tribe can be integrated into science learning in schools and universities.